Evolution of the cereals market in Romania in the period 2017-2021 - Diana Creţu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The paper presents the evolution of the market for the main cereal crops (wheat, corn, barley) at the national level in the period 2017-2021. These cereals, as well as others, constitute one of the groups of food carriers that occupy the largest share of the total food consumed, representing for the population the basic food present in the daily meals in different forms. In this study I proposed to analyze statistical data regarding cultivated areas, production, prices, consumption, import, export, the particularities of this market and based on I will draw a series of conclusions from them. The research method used in the study is statistical processing, economic analysis, but also the calculation of certain indicators based on the official data available on specialized websites. Due to the pedoclimatic conditions, Romania is considered a cereal country. Statistical data show that in 2021 Romania was the second largest exporter of cereals in the EU, the first place being corn.
Keywords: Q11; Q13; L11; 330; grain market; consumption; evolution